KAJIAN SIKLUS HIDUP LOLA (Trochus niloticus) DALAM MEREKONTRUKSI PENERAPAN TRADISI ADAT SASI DI PULAU HATTA KEPULAUAN BANDA - Idul La Muhamad; Ruwia Abdurasid; Ifandris Kaimudian; Kasman Renyaan; Rusdan Latora (Universitas Banda Naira, 2026)
This study aimed to examine the life cycle of the topshell (Trochus niloticus) in reconstructing the implementation of the traditional sasi management system on Hatta Island, Banda Islands. A descriptive qualitative approach was employed, combining a literature review and in-depth interviews. The literature review was conducted to identify information related to the species’ life cycle, growth, reproductive biology, length at first maturity, spawning season, population recruitment, including the implementation mechanisms and conservation principles underlying the sasi tradition. In-depth interviews were undertaken to obtain information on the ecological, management, historical, and socio-cultural aspects of sasi practices. The results indicated that the opening of sasi during October–November may not be fully aligned with the natural reproductive cycle of T. niloticus, as this period coincides with the late phase of the peak spawning season. Harvesting during this period may reduce the biomass of spawning adults, lower fertilization success, decrease larval production and juvenile recruitment, and ultimately diminish the long-term regenerative capacity of the population. Therefore, the opening of sasi is recommended to take place after the peak spawning season has ended, allowing the population to complete its reproductive processes before harvesting occurs. Furthermore, the minimum harvest size applied during sasi openings corresponds to the size at first gonadal maturity, indicating that the current harvest regulation is consistent with the principles of sustainable resource management. In addition, the sasi closure period provides sufficient time for multiple reproductive cycles to occur, facilitates larval settlement and juvenile recruitment, allows individuals to grow to reproductive adult size, and contributes to an increase in the biomass of spawning adults. These findings suggest that the traditional sasi system possesses strong ecological foundations that can support the sustainable management and conservation of T. niloticus populations on Hatta Island.